Skip to main content

Addition in the lambda calculus

I just spent a couple of very cold weeks in Anchorage Alaska.  I went out with a bunch of friends to a bar on the night prior to leaving, where I met up with an old friend (and listened to two other friends play music).  I started describing the lambda calculus to him since it is related to my work and he was curious what I was up to.  In any case I found myself unable to produce addition of the church numerals off the top of my head, which I found pretty disturbing since it shows that I probably didn't quite understand it in the first place.  Therefor I sat down this morning to see if I couldn't reconstruct it from first principles. 

It turns out that it is relatively easy. First, let us start with a bit of notation, and a description of the lambda calculus.  Since wikipedia describes the lambda calculus in detail, I'll just show how one procedes with calculations.  As examples let us start with the church numerals

1 = (λf x.f x)
2 = (λf x.f f x)
3 = (λf x.f f f x)
...
n = (λf x.fn x)

where fn means "f f ... f" n times.

The idea is that each numeral is represented by a lambda term.  The lambda term describes the arguments (f and x in this case) and the "body" in which we substitute the arguments when the are passed in.  An example of an "application" of a lambda term to an argument would be:

1 g = (λf x . f x) g => (λx . g x)

We pass in g, and replace every occurance of f in the body with g, and delete f from the list of variables.  we can continue to apply this term to another term

(λx . g x) y => g y

Which leads us to conclude that

1 g y => g y

Ok, so now that you've seen a few calculations, let us try to construct addition.  The first thing I tried to do is to construct the function +1.  Clearly, we want +1 n => (n+1).  n+1 is (λf x. f(n+1) x) which is also (λf x. f fn x).  Since n = (λf x. fn x) we need to somehow add another f.  The trick is to get the arguments to use the same symbols, and to remove the lambda abstraction.  We can do this by applying the church numeral to the symbols we want to use, in this case f and x.

(λf x. fn x) f x => fn x

So now we know how to get rid of the lambda abstraction.  Now we can add an f on the front, which will get us closer to n+1.

f (λf x. fn x) f x => f fn x

We are almost there.  Now we need to have the λf x part at the beggining so that we look like a church numeral.

(λf x. f (λf x. fn x) f x) => (λf x. f fn x) = (λf x. f(n+1) x)

Looking great so far!  Now we just need to be able to take the whole (λf x. fn x) form as an argument.  This turns out to be really easy, we just put a variable in it's place and add it to the front of the list of lambda arguments.

(λa f x. f a f x) (λf x . fn x) => (λf x. f (λf x. fn x) f x) => (λf x. f fn x)

This shows that (λa f x. f a f x) is the +1 function! 

+1 = (λa f x. f a f x)

Ok, so now that we have +1 can we get a function that takes an n and returns +n?  This would get us a long way towards addition.  We can call this function n->+n.

Ok, so we can guess what +n will look like easily.  It's going to look just like +1 except with n leading f's.

+n = (λa f x. fn a f x)

So we should try to figure out how to take the fn out of a church numeral, and place it there.  Well, we should apply the same trick of applying the church numeral to f and x so that we can extract the body.

(λf x . fn x) f x => fn x

ok, but really we want a to follow, based on +n, so instead of using x, let us apply the form to a.

(λf x . fn x) f a => fn a

Great!  Look how close we are. now we just need to abstract the a,f,x and place f x following it.
(λa f x. (λf x . fn x) f a f x) => (λa f x. fn a f x)

Ok, so now that we know how to take an n, and able to take the entire church numeral n as an a beta reduce it to n+1, let us abstract the n as an argument

(λb a f x. b f a f x)

Let us verify quickly that this function works.

(λb a f x. b f a f x) n =>
(λa f x. n f a f x) =>
(λa f x. (λf x. fn x) f a f x) =>
(λa f x. fn a f x)

Now, we can verify that this works on m, to obtain n+m as the +n function should:

(λa f x. fn a f x) m =>
(λf x. fn (λf x. fm x) f x) =>
(λf x. fn fm x) = (λf x. f(n+m) x) = n+m

Hooray! Not only did we find n->+n, but we have obtained the function "addition" for free.  Since, once we have the +n function we can apply it to m.  So we now have the function:

add = (λb a f x. b f a f x)

I haven't tried multiplication and exponentiation yet, but you are welcome to try!

Comments

Popular posts from this blog

Generating etags automatically when needed

Have you ever wanted M-. (the emacs command which finds the definition of the term under the cursor) to just "do the right thing" and go to the most current definition site, but were in a language that didn't have an inferior process set-up to query about source locations correctly (as is done in lisp, ocaml and some other languages with sophisticated emacs interfaces)?

Well, fret no more. Here is an approach that will let you save the appropriate files and regenerate your TAGS file automatically when things change assuring that M-. takes you to the appropriate place.

You will have to reset the tags-table-list or set it when you first use M-. and you'll want to change the language given to find and etags in the 'create-prolog-tags function (as you're probably not using prolog), but otherwise it shouldn't require much customisation.

And finally, you will need to run etags once manually, or run 'M-x create-prolog-tags' in order to get the initia…

Decidable Equality in Agda

So I've been playing with typing various things in System-F which previously I had left with auxiliary well-formedness conditions. This includes substitutions and contexts, both of which are interesting to have well typed versions of. Since I've been learning Agda, it seemed sensible to carry out this work in that language, as there is nothing like a problem to help you learn a language.

In the course of proving properties, I ran into the age old problem of showing that equivalence is decidable between two objects. In this particular case, I need to be able to show the decidability of equality over types in System F in order to have formation rules for variable contexts. We'd like a context Γ to have (x:A) only if (x:B) does not occur in Γ when (A ≠ B). For us to have statements about whether two types are equal or not, we're going to need to be able to decide if that's true using a terminating procedure.

And so we arrive at our story. In Coq, equality is som…

Formalisation of Tables in a Dependent Language

I've had an idea kicking about in my head for a while of making query plans explicit in SQL in such a way that one can be assured that the query plan corresponds to the SQL statement desired. The idea is something like a Curry-Howard in a relational setting. One could infer the plan from the SQL, the SQL from the plan, or do a sort of "type-checking" to make sure that the plan corresponds to the SQL.

The devil is always in the details however. When I started looking at the primitives that I would need, it turns out that the low level table joining operations are actually not that far from primitive SQL statement themselves. I decided to go ahead and formalise some of what would be necessary in Agda in order get a better feel for the types of objects I would need and the laws which would be required to demonstrate that a plan corresponded with a statement.

Dependent types are very powerful and give you plenty of rope to hang yourself. It's always something of…